PROBLEMS OF USING OF URBANIZED TERRITORIES GROUNDS AND RESOURCES OF THE UKRAINIAN GEOLOGICAL SPACE - KORNIEIENKO, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The areas resources of geological space of Ukraine are examined and the problems of the use of earths are analysed on the urbanized territories. It is set that intensive economic mastering of territories of city created the sharp deficit of free earths and that in such terms suitable under.